Correlation Between Blood Metabolite Profile and Spermatozoa Quality in Bali Semen by Micronutrient Addition - Dondatu, E.; Toleng, A. L.; Yusuf, M. (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2025)
The hematological profile and blood metabolite status are indicators of the physiological condition of livestock. This study aimed to determine the correlation between blood metabolite profiles (blood glucose and cholesterol) and sperm quality (motility and abnormality) in fresh Bali bull semen. Blood collection and semen sampling were conducted twice a week for 5 weeks. The collected blood and fresh semen were evaluated from two treatments: before and after the addition of micronutrients (including Zn, Se, and Vitamin E) in the feed. The parameters observed in this study were blood metabolite profiles (blood glucose and cholesterol levels) and sperm quality (percentage (%) motility and % abnormality of spermatozoa) before and after the addition of micronutrients. The data obtained were analyzed using simple linear regression and correlation tests. The results of this study showed that both treatments had a correlation between blood metabolite profiles and sperm quality in fresh Bali bull semen. Blood glucose levels correlated with sperm motility in fresh Bali bull semen, and good sperm motility values were obtained in all treatments before and after micronutrient administration in the feed. Cholesterol levels correlated with sperm abnormalities in fresh Bali bull semen, and all treatments before and after micronutrient addition in the feed showed abnormality values above the standard value. The blood metabolite profile (glucose and cholesterol) correlates with spermatozoa quality (motility and abnormalities) in fresh semen from Bali bull, where the addition of micronutrients in feed can increase spermatozoa motility but is not effective in suppressing the decrease in spermatozoa abnormalities. Keywords: Blood metabolite, blood sugar, cholesterol, spermatozoa quality